Effect of Absorbents on NOx Removal through Polyvinylidene Fluoride (PVDF) Hollow Fiber Membrane Modules - Irfan Purnawan; Sutrasno Kartohardjono; Levana Wibowo; Annisa Faiza Ramadhani; Woei Jye Lau; Arifina Febriasari (International Journal of Chemical Engineering)
NOx (NO and NO2) are air toxins that endanger life and represent a hazard to the environment, such as photochemical smog, global warming, acid rain, ozone depletion, and the occurrence of respiratory infections. Some technological strategies to diminish NOx emissions to meet regulations depend on two techniques: the dry process and the wet process. This study applies polyvinylidene fluoride (PVDF) hollow fiber membrane modules as a medium to remove NOx from solutions containing several absorbents such as hydrogen peroxide and nitric acid (H2O2-HNO3) solutions, sodium chlorite and sodium hydroxide (NaClO2-NaOH) solutions, and sodium chlorate and sodium hydroxide (NaClO3-NaOH) solutions. The experimental results showed that the oxidant’s strength influences NOx removal efficiency, where the absorbent solutions containing hydrogen peroxide had the highest removal efficiency as hydrogen peroxide is the most potent oxidant, followed by sodium chlorite and sodium chlorate. The three pairs of absorbents also gave a high NOx removal efficiency (above 90%), which means that all the absorbents used in the study are very potential to be used to diminish NOx via the wet process. NOx removal efficiency at the same feed gas flow rate increased as the number of fiber and absorbent concentrations is increased. However, NOx removal efficiency is reduced as the feed gas flow rate is increased at the same membrane module and absorbent concentration.